Determining the behavioural dose-response relationship of marine mammals to air gun noise and source proximity - Dunlop, R.; Noad, M.; McCauley, Robert; Scott-Hayward, L.; Kniest, E.; Slade, R.; Paton, D.; Cato, D. (The Company of Biologists Ltd., 2017)
The effect of various anthropogenic sources of noise (e.g. sonar, seismic surveys) on the behaviour of marine mammals is sometimes quantified as a dose-response relationship, where the probability of an animal behaviourally 'responding' (e.g. avoiding the source) increases with 'dose' (or received level of noise). To do this, however, requires a definition of a 'significant' response (avoidance), which can be difficult to quantify. There is also the potential that the animal 'avoids' not only the source of noise but also the vessel operating the source, complicating the relationship. The proximity of the source is an important variable to consider in the response, yet difficult to account for given that received level and proximity are highly correlated. This study used the behavioural response of humpback whales to n oise from two different air gun arrays (20 and 140 cubic inch air gun array) to determine whether a dose-response relationship existed. To do this, a measure of avoidance of the source was developed, and the magnitude (rather than probability) of this response was tested against dose. The proximity to the source, and the vessel itself, was included within the one-analysis model. Humpback whales were more likely to avoid the air gun arrays (but not the controls) within 3 km of the source at levels over 140 re. 1 µPa 2 s -1 , meaning that both the proximity and the received level were important factors and the relationship between dose (received level) and response is not a simple one.